2003
DOI: 10.2307/3803075
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Habitat Use by Kemp's Ridley Turtles in West-Central Florida

Abstract: The Kemp's ridley turtle (Lepidochelys kempii) is an endangered species whose recovery depends in part on the identification and protection of required habitats. We used radio and sonic telemetry on subadult Kemp's ridley turtles to investigate home-range size and habitat use in the coastal waters of west-central Florida from 1994 to 1996. We tracked 9 turtles during May-August up to 70 days after release and fou.ld they occupied 5-30 km 2 foraging ranges. Compositional analyses indicated that turtles used roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
(20 reference statements)
1
36
1
Order By: Relevance
“…Nearshore waters that have been studied include Apalachee Bay (Rudloe et al 1991;Campbell 1996), Deadman Bay (Barichivich 2006), Cedar Keys/Waccasassa Bay (Schmid and Ogren 1990;Schmid 1998;Schmid et al 2002Schmid et al , 2003, Tampa Bay (Nelson 2000), Charlotte Harbor Estuary (Schmid 2011), and Ten Thousand Islands/Gullivan Bay Schmid 2004, 2005). Details of these investigations are presented in the following paragraphs.…”
Section: Neritic Juvenile Life History and Distribution For Gulf Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearshore waters that have been studied include Apalachee Bay (Rudloe et al 1991;Campbell 1996), Deadman Bay (Barichivich 2006), Cedar Keys/Waccasassa Bay (Schmid and Ogren 1990;Schmid 1998;Schmid et al 2002Schmid et al , 2003, Tampa Bay (Nelson 2000), Charlotte Harbor Estuary (Schmid 2011), and Ten Thousand Islands/Gullivan Bay Schmid 2004, 2005). Details of these investigations are presented in the following paragraphs.…”
Section: Neritic Juvenile Life History and Distribution For Gulf Of Mmentioning
confidence: 99%
“…In a related investigation, juvenile Kemp's ridleys were studied in Waccasassa Bay from May through August 1994 and May through November 1995 (Schmid et al 2002(Schmid et al , 2003. Turtles occupied foraging areas ranging from 5 to 30 km 2 (1.9 to 11.6 mi 2 ) in size, and they used rock outcroppings more than expected (Schmid et al 2003).…”
Section: Neritic Juvenile Life History and Distribution For Gulf Of Mmentioning
confidence: 99%
“…Similarly, juvenile green sea turtles monitored using sonic telemetry for several months in inshore (Mendonça 1983) and nearshore (Makowski C et al 2006) waters occupied home ranges between 0.48-5.06 km 2 (Mendonça 1983). Juvenile Kemp's ridley turtles followed using radio and sonic telemetry restricted their foraging activities to areas ranging from 5 to 30 km 2 (Schmid 2000;Schmid et al 2003). The 10-80 km 2 foraging ranges estimated for juvenile loggerheads tracked using radio telemetry for 2-66 days (mean = 26.5 days) in a coastal bay are far larger than those found for other turtle species (Byles 1988).…”
Section: Site Fidelity Of Sea Turtlesmentioning
confidence: 99%
“…Juvenile loggerheads leading a pelagic existence grow at rates of 1-2 inches (2.9-5.4 cm) per year (Bjorndal et al 2003;Snover 2002) over a period as long as 7-12 years ) before moving to more coastal habitats. Recent studies have suggested that not all loggerhead sea turtles follow the model of circumnavigating the North Atlantic Gyre as pelagic juveniles, followed by permanent settlement into benthic environments (Bolten and Witherington 2003;Laurent et al 1998).…”
Section: Life History Informationmentioning
confidence: 99%
“…Kernel densities were summarized as 95% and 50% utilization distributions (UD), which are respectively denoted as home ranges and core activity areas within this study (Worton 1989). UDs for each turtle were constructed using GPS locations that were temporally separated by at least 4 h in order to reduce serial auto cor relation (Swihart & Slade 1987, Hansteen et al 1997, Schmid et al 2003; the majority of turtle locations were separated by > 24 h. All UDs were computed within ArcGIS 9.3 using the HRT Tools extension (http://flash. lakeheadu .…”
Section: Home Range Estimationmentioning
confidence: 99%